Fundamental Principles and Relevance of Reviewing Factual Actions within the Authority of the State Administrative Court - Suroto, Suroto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The State Administrative Court (PTUN) plays a critical role in ensuring lawful and accountable governance. Traditionally, its purview focused on reviewing legal aspects of administrative decisions. However, recent developments grant the State Administrative Court authority to examine factual actions taken by the government. This article explores the fundamental principles underpinning this expanded authority. It delves into concepts like legality, proportionality, and good governance, analyzing how the State Administrative Court ensures these principles are upheld in factual actions. The article further analyzes regulations governing the State Administrative Court of various countries, including France, Netherlands, and England. By identifying similarities and variations in how these nations empower their SACs, the article presents a helpful perspective into best practices and potential challenges. Thus, this article offers valuable insights into the evolving role of SACs in promoting a more just and transparent administrative system.